Evaluation of the Simak-BMN Application on Data Validity in Financial Report Administration - Maryam*, Maryam; Kian, Lia; Istianda, Meita (Riwayat: Educational Journal of History and Humanities, 2024)
https://jurnal.usk.ac.id/riwayatThis research aims to evaluate the SIMAK BMN application on the validity of data in the administration of Financial Reports at the Bangka Regency Ministry of Religion Office. In line with Presidential Regulation Number 81 of 2010 concerning Grand Design for Bureaucratic Reform 2010-2025, one of the main objectives is the creation of Good Governance, which means the implementation of good, clean government, free of corruption, collusion, and nepotism. Good governance can be achieved by implementing a budget that is transparent and accountable. The research used is qualitative research with data collection techniques carried out by interviews, observation, and documentation. Interviews were conducted with officials at the Bangka Regency Ministry of Religion Office and application operators within the Bangka Regency Ministry of Religion. Based on the results of field analysis, it was found that the data produced from the SIMAK BMN application did not reflect the actual situation. From the results of this research, it is hoped that the Working Unit Leaders will carry out routine supervision of asset administration, place competent human resources who are assigned specifically to manage assets/not additional work/multitasking, and improve the quality of the application system so that it is easier to understand considering that this application is used by all Ministries/Institutions whose budgeting comes from the APBN.